Sustainable development versus urban sprawl: A Landsat imagery analysis of ecological impact in Savar Upazila, 2011–2022 - Taslima Akter Sathe; Syed Hafizur Rahman (Case Studies in Chemical and Environmental Engineering)
This study investigates the ecological impacts of urban expansion in Savar Upazila, adjacent to Dhaka City, from 2011 to 2022. Utilizing Landsat (Level 2) imagery and the Time-weighted Dynamic Time Warping (TWDTW) classification method, the research assesses urban sprawl with high accuracy (98.87%, 96.01%, and 96.53% for 2011, 2015, and 2022, respectively). Urban expansion was predominantly through extension, with a 9.19% increase in urban areas. The study also calculates Urban Hotspot Zones (UHs) and the Urban Thermal Field Variance Index (UTFVI) from Land Surface Temperature (LST) data, highlighting the growth of urban hotspots. The Partial Least Squares Regression (PLSR) reveals that development type affects the Urban Heat Island effect and extension is the most determining factor for ecological change. A local level analysis reveals that nearly all unions, except Shimulia and Pathalia, experienced a rise in areas with adverse ecological conditions, with Tetulihora, Amin Bazar, Ashulia, and nearby areas facing the most significant ecological deterioration due to urbanization (∼50%). The findings underscore a considerable decline in the region's ecological health due to urban expansion, urging policymakers to integrate stable ecological zones into urban planning for sustainable development.